Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Perilaku Keuangan Syariah pada Mahasiswa FEBI UINSU di Kota Medan - Nurganti Nurganti; Ria Armayani Hasibuan, Reni; Ahmadi Bi Rahmani, Nur (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the influence of financial literacy and lifestyle on Islamic financial behavior in students of the Faculty of Islamic Economics and Business (FEBI) of the State Islamic University of North Sumatra (UINSU) in Medan City. The type of research used is quantitative with an active student population majoring in Islamic Economics class of 2022 and 2023. The sample was determined through a purposive sampling technique with a total of 100 respondents. Data was collected using questionnaire instruments and analyzed through the stages of data quality test, classical assumption test, multiple linear regression, and hypothesis test. The results of the study show that financial literacy has a positive and significant effect on Islamic financial behavior, which means that the better a person's financial literacy, the better the Islamic financial behavior shown. On the other hand, lifestyle variables do not have a significant effect on Islamic financial behavior. These findings affirm the importance of increasing financial literacy among students as the main factor in shaping rational, wise, and Islamic financial behavior, while lifestyle is not the main determinant in the context of this study.